Pelatihan Senior PKP-PK Bagi Personel Bandar Udara: Upaya Peningkatan Kompetensi dalam Penanganan Keadaan Darurat Penerbangan - Wildan Nugraha; Yeti Komalasari; Direstu Amalia; Fadhilla Nina Rizkyanti; Arif Triyanto; Anton Abdullah (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
Aviation Rescue and Firefighting (ARFF) personnel play a crucial role in supporting aviation safety by implementing rescue and emergency response measures at airports. Continuous competency development of ACR personnel is essential to ensure readiness to address developments in aviation technology, the complexity of airport operations, and the demands of safety regulations. This community service activity took the form of ACR Senior Training, organized by the Palembang Aviation Polytechnic for 19 ACR personnel from 18 Airport Operational Units (UPBU). The training used a Competency-Based Training (CBT) approach, consisting of 29 learning materials, totalling 102 hours of theory and 98 hours of practical training. Evaluation was conducted through pre-tests, post-tests, practical assessments, and participant satisfaction surveys. The results showed an increase in participant competency, as evidenced by an average score of 85 in the pre-test to 96 in the post-test, a 12.94% increase. Furthermore, participant satisfaction with the training reached 95%. These results demonstrate that the training improved participants' knowledge, skills, and professional attitudes in carrying out PKP-PK operational tasks. This activity positively contributed to strengthening the competence of airport human resources and supported increased preparedness in handling emergencies to achieve sustainable aviation safety